О единственности решений задачи Дирихле в круге для дифференциальных уравнений четвертого порядка в вырожденных случаях - Буряченко, Е.А. (Нелинейные граничные задачи, 2000)
In present paper a necessary and sufficient conditions of the nontrivial solvability of the homogeneous Dirichlet problem in the disk for linear differential equations of the fourth order with constant complex coefficients and homogeneous degenerated symbol in general state are received.